Geoestatística na avaliação dos atributos físicos em latossolo sob floresta nativa e pastagem na Região de Manicoré, Amazonas - Aquino, Renato Eleotério De [UNESP]; Campos, Milton César Costa; Marques Júnior, José [UNESP]; Oliveira, Ivanildo Amorim De [UNESP]; Mantovaneli, Bruno Campos; Soares, Marcelo Dayron Rodrigues (Sociedade Brasileira de Ciência do Solo, 2014)
The use of geostatistical techniques allows detection of the existence of dependence and the spatial distribution of soil properties, thus constituting an important tool in the analysis and detailed description of the behavior of soil physical properties. The aim of the present study was to use geostatistics in assessment of physical properties in a Latossolo (Oxisol) dystrophic under native forest and pasture in the Amazon region of Manicore. Grids with of 70 x 70 m were established in native forest and pasture, and points were marked in these grids spaced at every 10 m, for a total of 64 points. These points were then georeferenced and in each one, soil samples (128) were collected at the depths of 0.00-0.20 and 0.40-0.60 m for a survey of their physical properties. These grids are parallel at a distance of 100 m from one another. The following determinations were made: texture, bulk density and particle density, macroporosity, microporosity, total porosity and aggregate stability in water. After tabulating the data, descriptive statistical analysis and geostatistical analysis were performed. The pasture had a slight variation in its physical properties in relation to native forest, with a high coefficient of variation and weak spatial dependence. The scaled semivariograms were able to satisfactorily reproduce the spatial behavior of the properties in the same pattern as the individual semivariograms, and the use of the parameter range of the semivariogram was efficient for determining the optimal sampling density for the environments under study. The geostatistical results indicate that the removal of native forest for establishing pasture altered the natural variability of the physical properties.

A utilização das técnicas geoestatísticas permite detectar a existência da dependência e distribuição espacial dos atributos do solo, constituindo importante ferramenta na análise e descrição detalhada do comportamento dos atributos físicos do solo. Este trabalho teve como objetivo o uso da geoestatística na avaliação dos atributos físicos em Latossolo sob floresta nativa e pastagem na região de Manicoré no Amazonas. Nas áreas de floresta nativa e pastagem, foram estabelecidas malhas com dimensão 70 × 70 m e demarcados pontos nessas malhas espaçados a cada 10 m, totalizando 64 pontos. Esses pontos foram georreferenciados e, em seguida, foram feitas as coletadas de solo em cada ponto da malha nas camadas de 0,00-0,20 e 0,40-0,60 m para determinação dos atributos físicos, totalizando 128 amostras de solo em cada malha. Essas malhas encontram-se paralelas com uma distância uma da outra de 100 m e o solo nessas áreas é classificado como Latossolo. Determinaram-se textura, densidade do solo e de partículas, macroporosidade, microporosidade, porosidade total e estabilidade dos agregados em água. Após a tabulação dos dados, foram realizadas análises estatísticas descritivas e geoestatística. A pastagem apresentou leve variação nos seus atributos físicos em relação à floresta nativa, com coeficiente de variação alto e dependência espacial fraca. Os semivariogramas escalonados conseguiram reproduzir de forma satisfatória o comportamento espacial dos atributos no mesmo padrão dos semivariogramas individuais, e o uso do parâmetro alcance do semivariograma mostrou-se eficiente para determinar a densidade amostral ideal para os ambientes em estudo. Os resultados geoestatísticos indicaram que a retirada da floresta nativa para a implantação da pastagem alterou a variabilidade natural dos atributos físicos.
Geostatistics in assessment of physical properties in a latossolo (oxisol) under native forest and grassland in Manicoré, Amazonas, Brazil
Keywords: Geostatistics; Spatial dependence; sampling density; southern Amazon; Geoestatística; Dependência espacial; densidade amostral; sul do Amazonas